2000
DOI: 10.1097/00004872-200018110-00008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan of predisposing loci for increased diastolic blood pressure in Finnish siblings

Abstract: Our results establish the role of the AT1 locus, on a genome-wide scale, as a major contributing locus to essential hypertension in this study sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 21 publications
4
62
0
Order By: Relevance
“…11 A Finnish study based on 47 families of concordant sib pairs (mostly twins) with early-onset hypertension (onset before age 50 years) showed linkage to chromosome 3q (near Type 1 angiotensin II receptor) and suggestive linkage to 2q, 22q, and Xp. 12 Our genome scan shows evidence of linkage, though not significant, supporting previously linked loci on chromosomes 2, 4,8 11, 10 and 17 6 (Table 3). On chromosome 18 our genome scan identifies a locus different from previously reported loci of essential hypertension.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…11 A Finnish study based on 47 families of concordant sib pairs (mostly twins) with early-onset hypertension (onset before age 50 years) showed linkage to chromosome 3q (near Type 1 angiotensin II receptor) and suggestive linkage to 2q, 22q, and Xp. 12 Our genome scan shows evidence of linkage, though not significant, supporting previously linked loci on chromosomes 2, 4,8 11, 10 and 17 6 (Table 3). On chromosome 18 our genome scan identifies a locus different from previously reported loci of essential hypertension.…”
Section: Discussionsupporting
confidence: 84%
“…3 There have been several genomewide linkage scans of familial blood pressure distribution/variation 4 -10 and for essential hypertension. [11][12][13] Here, we report significant linkage to chromosome 18q in our genomewide linkage study of 490 Icelandic hypertensive patients in 120 families.…”
mentioning
confidence: 53%
“…However, a comparison with linkage scans for resting hemodynamic phenotypes reveals some common chromosomal areas. The submaximal exercise SV and Q training response QTL in chromosome 2q31 in the present study maps to the same region where previous studies have reported QTLs for familial dilated cardiomyopathy (31) and for resting diastolic blood pressure in Old Order Amish (16) and in a geographically defined subgroup of Finnish dizygotic twins (21). The linkage with baseline SV50 and Q50 in chromosome 10p14 coincides with a QTL for arrhythmogenic right-ventricular dysplasia (20) and a linkage region for resting systolic blood pressure in the Quebec Family Study (26).…”
Section: Discussionsupporting
confidence: 72%
“…30 However, no reported information has suggested a relationship between the (P)RR and hypertension in humans. Recently, a population study showed a significant association between (P)RR gene polymorphisms and blood pressure levels in 1112 Japanese subjects.…”
Section: Genetic Analyses In Population Studiesmentioning
confidence: 99%